Handbook of research on e-government in emerging economies : adoption, e-participation, and legal frameworks - Bwalya, Kelvin Joseph, 1979-; Zulu, Saul, 1956- (Hershey, PA : Information Science Reference, 2012)
"This book is a collection of knowledge on contemporary experiences on technological, societal and legal setups of e-Government implementation in emerging economies"--Provided by publisher.